Perceptual basemaps reloaded: The role basemaps play in eliciting perceptions. Issue 2 (17th April 2019) - Bounds, Paulina; Sutherland, Charles J.
Abstract : This article describes the influence of various basemaps in Perceptual Dialectology, on the national and state levels. The 180 perceptual maps of the United States and Tennessee were divided into six types of basemaps; tabulated results show that basemaps play a different role on the national and state level. On the national level, basemaps that have features reminiscent of boundaries (state lines or interstates) bias the respondents' answers. On the state level, on the other hand, the map features do not seem to influence the results in any discernible way: at times the informants seemingly go against the details present on the basemap. This striking difference indicates that, though the respondents rely on basemap details at the national level, where they may not have enough experience with the whole country, they don't pay much attention to the state-level basemap details as they follow their own more detailed ideas about perceptions.